ORGANIZATIONAL IMPLEMENTATION IN STUDENT LEADERSHIP EXTRA ACTIVITIES OF THE FACULTY OF SOCIAL SCIENCES, UIN NORTH SUMATRA - Nafan Jamil Polem; Nursapia Harahap (KABILAH : Journal of Social Community, 2022)
Abstract: Humans will find it difficult if everything is done individually. Organization is a container formed based on human ideas and thoughts to unite individuals into a group to one goal. Therefore, these groups need a leader as amotivator who is able to be responsible and motivate members for the smooth running of the organization. Communication is the main tool needed in running an organization. Therefore, this journal will answer the question of how leadership communication in an organization Keywords: Social Science, Leadership, Organizational Communication